Current Advancement by Membrane Technology: A Review - Mohd Syafiq, Sharip; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; Muhammad Atif, Mohamed Azmi; Farhana, Aziz; Wan Norharyati, Wan Salleh (Akademi Baru, 2019)
In the current years, hydrogen (H2) which is a high quality carrier for clean energy attracts rejuvenated and ever-increasing attention around the world mainly due to the advancement of fuel cells, environmental burdens as well as global climate change issues. Purification and separation technologies are important in the thermochemical processes of H2 production from fossil fuels. The membrane reactors demonstrate reliable assurances in shifting the equilibrium whenever the shift reaction of water-gas is involved in transforming monoxide into H2. Membranes are also crucial in the following purification of H2. In this article, recent developments in each porous ceramic membranes and dense section metal are reviewed while their separation properties and performance in membrane reactor systems are compared. Discussions of this work will focus on the relationship and significance of membrane technology for application in the new generation zero-emission power technologies.